Down-regulation of PRKCB1 expression in Han Chinese patients with subsyndromal symptomatic depression. (October 2015) - Guo, Xiaoyun; Li, Zezhi; Zhang, Chen; Yi, Zhenghui; Li, Haozhe; Cao, Lan; Yuan, Chengmei; Hong, Wu; Wu, Zhiguo; Peng, Daihui; Chen, Jun; Xia, Weiping; et al.
Abstract: Background: Subsyndromal symptomatic depression (SSD) is a common disease with significant social dysfunction. However, SSD is still not well understood and the pathophysiology of it remains unclear. Methods: We classified 48 candidate genes for SSD according to our previous study into clusters and pathways using DAVID Bioinformatics Functional Annotation Tool. We further replicated the result by using real-time Quantitative PCR (qPCR) studies to examine the expression of identified genes (i.e., STAT5b, PKCB1, ABL1 and NRAS) in another group of Han Chinese patients with SSD (n = 50). We further validated the result by examining PRKCB1 expression collected from MDD patients (n = 20). To test whether a deficit in PRKCB1 expression leads to dysregulation in PRKCB1 dependent transcript networks, we tested mRNA expression levels for the remaining 44 genes out of 48 genes in SSD patients. Finally, the power of discovery was improved by incorporating information from Quantitative Trait (eQTL) analysis. Results: The results showed that the PRCKB1 gene expression in peripheral blood mononuclear cells (PBMC) was 33.3% down-regulated in SSD patients (n = 48, t = 3.202, p = 0.002), and a more dramatic (n = 17, 49%) down-regulation in MDD patients than control (n = 49, t = 2.114, p = 0.001). We also identified 37 genes that displayed a strong correlation with PRKCB1 mRNA expression levels in SSD patients. The expression of PRKCB1 was regulated by multiple single nucleotide polymorphisms (SNPs) both at the transcript level and exon level. Conclusions: In conclusion, we first found a significant decrease of PRCKB1 mRNA expression in SSD, suggesting PRKCB1 might be the candidate gene and biomarker for SSD. Graphical abstract: Highlights: PRCKB1 gene expression was down-regulated in subsyndromal symptomatic depression (SSD) patients, and a more dramatic down-regulation in major depression patients. It suggested PRKCB1 might be the candidate gene and biomarker for SSD. 37 genes displayed a strong correlation with PRKCB1 mRNA expression levels in SSD patients. It suggested a deficit in PRKCB1 expression leads to dysregulation in PRKCB1 dependent transcript networks. Quantitative Trait (eQTL) analysis showed the expression of PRKCB1 was regulated by multiple single nucleotide polymorphisms (SNPs). It suggested that PRKCB1 might be functional and thus have a potential role to play in disease.